2021
DOI: 10.1002/ange.202014331
|View full text |Cite
|
Sign up to set email alerts
|

Facile Access to an Active γ‐NiOOH Electrocatalyst for Durable Water Oxidation Derived From an Intermetallic Nickel Germanide Precursor

Abstract: Identifying novel classes of precatalysts for the oxygen evolution reaction (OER by water oxidation) with enhanced catalytic activity and stability is a key strategy to enable chemical energy conversion. The vast chemical space of intermetallic phases offers plenty of opportunities to discover OER electrocatalysts with improved performance. Herein we report intermetallic nickel germanide (NiGe) acting as a superior activity and durable Ni‐based electro(pre)catalyst for OER. It is produced from a molecular bis(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 112 publications
1
31
0
Order By: Relevance
“…[ 56 ] However, they closely resemble the Raman features observed for nickel‐, cobalt‐, and iron‐containing layered double hydroxides that form during the OER and can be assigned to the δ(FeO) (473 cm −1 ) and ν(FeO) (558 cm −1 ) vibration modes of edge sharing [FeO 6 ] octahedra (insets of Figure 2a). [ 30,57,58 ] The band at 240 cm −1 and the one at around 640 cm −1 are most likely caused by the frozen electrolyte and the FTO substrate, respectively. [ 59–61 ] The XANES spectrum of the pristine FeSi powder shows a slow rise in absorption and no edge maximum as expected due to the soft silicon ligands (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 56 ] However, they closely resemble the Raman features observed for nickel‐, cobalt‐, and iron‐containing layered double hydroxides that form during the OER and can be assigned to the δ(FeO) (473 cm −1 ) and ν(FeO) (558 cm −1 ) vibration modes of edge sharing [FeO 6 ] octahedra (insets of Figure 2a). [ 30,57,58 ] The band at 240 cm −1 and the one at around 640 cm −1 are most likely caused by the frozen electrolyte and the FTO substrate, respectively. [ 59–61 ] The XANES spectrum of the pristine FeSi powder shows a slow rise in absorption and no edge maximum as expected due to the soft silicon ligands (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…[ 20,24 ] Recently, for the OER, non‐noble‐metal‐based intermetallics showed remarkable activities and it was revealed that, despite their inherent thermodynamic stability under ambient conditions, some undergo partial corrosion during the OER evolving active oxidized sites interconnected to the conductive precursor phase. [ 25–30 ] Also an intermetallic nickel silicide has been investigated which showed only moderate OER activities probably due to the absence of highly active iron sites. [ 31 ]…”
Section: Introductionmentioning
confidence: 99%
“…The nanoparticular intermetallic phases proved to be very efficient during alkaline OER exhibiting low overpotentials and prolonged stability of three weeks. 105 A chemical reduction approach was also utilized to derived phase pure FeSn 2 nanocrystals recorded one of the lowest η 10 of 197 mV (Tafel slope = 33 mV dec -1 ) with the stability of over 60 h. This system was found to be even superior to analogous Fe-, FeNi as well as noble-metal-based materials. 102 An up-todate table on the activity parameters of intermetallics has been provided in Table 2.…”
Section: Non-noble Metal-based Intermetallicsmentioning
confidence: 98%
“…In comparison to pure Fe-based materials, the Fe 6 Ge 5 showed superior OER activity with η 10 of 221 mV and a Tafel slope of 32 mV dec -1 and was constantly mediated the reaction under high potential for more than a day. In continuation, we further developed synthetic strategies to obtain NiGe 105 and FeAs 149 from molecular SSPs. The nanoparticular intermetallic phases proved to be very efficient during alkaline OER exhibiting low overpotentials and prolonged stability of three weeks.…”
Section: Non-noble Metal-based Intermetallicsmentioning
confidence: 99%
See 1 more Smart Citation